THE USE SQ3R METHOD TO IMPROVE STUDENTS’ READING COMPREHENSION - Siti Rohmah Tri Wardhani (English Education Department Slamet Riyadi University Surakarta, 2019)
This research aims at improving students’ reading comprehension in MAN 1 Surakarta especially to identify the main idea, the meaning of vocabulary, detail information, reference and inference in narrative text by using (Survey, Question, Read, Recite, and Review) SQ3R method. This method was Classroom Action Research and there were 2 cycles. The procedures are namely planning, acting, observing, and reflecting. Test namely pre test and post test and non-test namely observation, interview, questionnaire, and documentation techniques were used in collecting data. The techniques of analyzing data were interpreted using qualitative and quantitative techniques. The result of SQ3R method could improve the students’ reading comprehension. It can be seen through the student’s score and there were significant improvement in teaching and learning process. The mean of pre test was 55.85, post test 1 was 71.75, and post test 2 was 86.5. The result of t-table could be seen from t0 > tt in significance 5% 9.79 > 1.69 in cycle 1 and 10.1>1.69 in cycle 2. The condition became active, joyful, active discussion, communicative, and conducive. The students were more active, confident, and their motivation increased. It can be constructed that SQ3R method could improve students’ reading comprehension. Keywords: Classroom Action Research; improving; Reading Comprehension; SQ3R method.